2018
DOI: 10.1103/physrevb.97.115126
|View full text |Cite
|
Sign up to set email alerts
|

Statistically induced topological phase transitions in a one-dimensional superlattice anyon-Hubbard model

Abstract: We theoretically investigate topological properties of the one-dimensional superlattice anyon-Hubbard model, which can be mapped to a superlattice bose-Hubbard model with an occupationdependent phase factor by fractional Jordan-Wigner transformation. The topological anyon-Mott insulator is identified by topological invariant and edge modes using exact diagonalization and density-matrix renormalization-group algorithm. When only the statistical angle is varied and all other parameters are fixed, a statistically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The K-theory and group theory have been used to classify topological insulators, semimetal, and superconductors under the internal (nonspatial) symmetry and space group [44][45][46][47]. On the other hand, the superlattice potential [20,21,23,25,26,28,[48][49][50][51], periodically modulated hopping [22,24,27,52,53], and periodically driven field [6,7,34,35,[54][55][56] have been the simple and elegant avenues towards realizing fascinating topological phases. The Su-Schrieffer-Heeger (SSH) model [52], diagonal and off-diagonal Aubry-Andre or Harper (AAH) model [48,53], and topological Floquet systems [54][55][56] with their counterpart interaction systems are object of considerable theoretical and experimental interest.…”
Section: Introductionmentioning
confidence: 99%
“…The K-theory and group theory have been used to classify topological insulators, semimetal, and superconductors under the internal (nonspatial) symmetry and space group [44][45][46][47]. On the other hand, the superlattice potential [20,21,23,25,26,28,[48][49][50][51], periodically modulated hopping [22,24,27,52,53], and periodically driven field [6,7,34,35,[54][55][56] have been the simple and elegant avenues towards realizing fascinating topological phases. The Su-Schrieffer-Heeger (SSH) model [52], diagonal and off-diagonal Aubry-Andre or Harper (AAH) model [48,53], and topological Floquet systems [54][55][56] with their counterpart interaction systems are object of considerable theoretical and experimental interest.…”
Section: Introductionmentioning
confidence: 99%
“…These proposals are based on the fractional Jordan-Wigner transformation by mapping anyons to bosons with a density-dependent tunneling parameter. Some exotic properties of one-dimensional anyons [29][30][31][32][33] closely related to the statistical angle have been revealed, such as the statistically induced ground state phase transition 26,34,35 , the asymmetry of two-body correlations in the momentum space 36 , and the spatially asymmetric particle transport of interacting anyons 37 . However, to the best of our knowledge, the MBL properties of anyons in disordered systems have not been studied in literature.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate the above issues in context of the paradigmatic Su-Schrieffer-Heeger (SSH) model for polyacetylene [10,11] that stabilises symmetry protected topological boundary modes. We examine an interesting tuning parameter that is of relevance in context of recent experimental [43,44] and theoretical [45][46][47] developments -the generalised algebra of the interacting fermions -and study it in context of two coupled SSH chains as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…(1)), allows the degrees of freedom to smoothly transform from being fermionic to (hard core) bosonic and vice-versa in one spatial dimension. Such degrees of freedom, referred as pseudofermions [47], are generalizations of "anyons" in one dimension [45,. Quite remarkably, this anyonic physics has been recently realized experimentally in a cold atomic setting [44].…”
Section: Introductionmentioning
confidence: 99%